2005
DOI: 10.1097/01.wnf.0000183446.58529.30
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Clozapine and Ziprasidone in Treatment-Resistant Schizophrenia

Abstract: The combined application of clozapine and ziprasidone follows a neurobiologic rationale and appears to be safe and well tolerated without increasing the risk of side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 31 publications
0
23
0
1
Order By: Relevance
“…Finally, Honer et al treated groups of 34 patients over a period of eight weeks and reported that the addition of risperidone did not improve the symptoms in patients with severe schizophrenia [20] . Ziprasidone has been added to clozapine in attempts to reduce metabolic side eff ects [19,25] and to optimize antipsychotic effi cacy [39,40] .…”
mentioning
confidence: 99%
“…Finally, Honer et al treated groups of 34 patients over a period of eight weeks and reported that the addition of risperidone did not improve the symptoms in patients with severe schizophrenia [20] . Ziprasidone has been added to clozapine in attempts to reduce metabolic side eff ects [19,25] and to optimize antipsychotic effi cacy [39,40] .…”
mentioning
confidence: 99%
“…51 We identified nine noncontrolled observational trials comparing antipsychotic polypharmacy to monotherapy in samples with established treatment resistance to trials of a single antipsychotic (Table 1). [53][54][55][56][57][58][59][60][61] All studies were of patients with schizophrenia or schizoaffective disorder. Eight of the trials reported significant improvement in reduced symptoms with the addition of a second antipsychotic.…”
Section: Samples With Established Treatment Resistance To Antipsychotmentioning
confidence: 99%
“…Eight of the trials reported significant improvement in reduced symptoms with the addition of a second antipsychotic. 53,[55][56][57][58][59][60][61] Of the eight studies that examined side effects, four reported no change with the addition of a concurrent antipsychotic. 53,54,59,60 Three studies reported increased side effects with the addition of another antipsychotic, [56][57][58] whereas one study reported a decrease in sedation.…”
Section: Samples With Established Treatment Resistance To Antipsychotmentioning
confidence: 99%
See 2 more Smart Citations